2016
DOI: 10.2500/ajra.2015.29.4251
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic Effects of Anti-Interleukin-33 are Associated with Suppression of Immunoglobulin Light Chain and Inducible Nitric Oxide Synthase

Abstract: The antiallergic effect of anti-IL-33 can be explained by suppression of IgFLC and NOS2 in a murine model of allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Apart from the small molecules with specific target in the IL-33/ST2 axis as mentioned above, blocking IL-33 and its receptor by monoclonal antibodies is the major therapeutic approach in targeting IL-33/ST2 axis of allergic inflammatory diseases, and serval clinical trials are in progress (105, 107111). The main side effect of monoclonal antibody administration is the risk of immune reactions such as serum sickness and acute anaphylaxis which may be fatal (112, 113).…”
Section: Il-33 As the New Therapeutic Target For Allergic Diseasesmentioning
confidence: 99%
“…Apart from the small molecules with specific target in the IL-33/ST2 axis as mentioned above, blocking IL-33 and its receptor by monoclonal antibodies is the major therapeutic approach in targeting IL-33/ST2 axis of allergic inflammatory diseases, and serval clinical trials are in progress (105, 107111). The main side effect of monoclonal antibody administration is the risk of immune reactions such as serum sickness and acute anaphylaxis which may be fatal (112, 113).…”
Section: Il-33 As the New Therapeutic Target For Allergic Diseasesmentioning
confidence: 99%
“…COX-2 inhibition has an antiallergic effect via the downregulation of prostaglandin D2 [ 24 ], and thus, the antiallergic effect of anti-IL-33 might also be related to COX-2 inhibition. On the other hand, iNOS protein levels were not significantly different between the four groups, although it tended to be lower in group D. In our previous study on mice with allergic asthma, iNOS protein expression was significantly higher in mice with allergic asthma and this increase was effectively suppressed by treating lung tissues with anti-IL-33 [ 25 ]. However, the role of iNOS and nitric oxide in the glomerulus have been extensively debated.…”
Section: Discussionmentioning
confidence: 99%
“…Other work published in this issue of the American Journal of Rhinology & Allergy includes a murine model of allergic rhinitis by Park et al 3 In this study, the mice were sensitized and then treated with anti-IL 33. By blocking this cytokine, the authors found that immunoglobulin free light chain expression was decreased and that nitric oxide synthase 2 was also decreased.…”
mentioning
confidence: 99%